A compromise between piezoelectricity and transparency in KNN-based ceramics: The dual functions of Li2O addition. Issue 6 (June 2020) - Ren, Xiaodan; Peng, Zhanhui; Chen, Bi; Shi, Qiangqiang; Qiao, Xiaoshuang; Wu, Di; Li, Guorong; Jin, Li; Yang, Zupei; Chao, Xiaolian
Abstract: Transparent ceramics with good electrical performance have recently drawn broad interest as promising multifunctional materials. Here, we report that a superior transmittance ( T = 75 % at 2000 nm) and good piezoelectricity ( d 33 ∼ 150 pC/N) can be simultaneously realized in 0.93K0.5 Na0.5 NbO3 -0.07SrZrO3 (KNN-SZ) ceramics by Li2 O regulation. The effect of Li2 O regulation has two parts: first, the presence of Li2 O facilitates the grain growth of KNN-SZ, considering that it melts at a relatively low temperature as a proper sintering aid; second, the introduced Li + causes local lattice distortion, resulting in the coexistence of orthogonal and tetragonal ( O–T ) phases. The enlarged grains reduce the light scattering by grain boundaries for a higher optical transmittance; meanwhile, large grains stand as a prerequisite for the macroscopic domain structure favoured for decent piezoelectricity, which could also be partly caused by the coexistence of O–T phases. We believe that these findings might make KNN-based ceramics a preferable candidate for optoelectronic devices.